Magnitude of the 1920 Haiyuan Earthquake Reestimated Using Seismological and Geomorphological Methods. Issue 8 (13th August 2020) - Ou, Q.; Kulikova, G.; Yu, J.; Elliott, A.; Parsons, B.; Walker, R.
Abstract: Reported magnitudes ranging between 7.8 and 8.7 highlight a confusion about the true size of the 1920 Haiyuan earthquake, the largest earthquake recorded in the northeast Tibetan Plateau. We compiled a global data set of previously unlooked‐at historical seismograms and performed modern computational analyses on the digitized seismic records. We found the epicenter to be near Haiyuan town and obtained a moment magnitude of M W =7.9±0.2. Following traditional approaches, we obtained m B =7.9±0.3 with data from 21 stations and M S (20)=8.1±0.2 with data from three stations. Geomorphologically, we mapped the surface rupture and horizontal offsets on high‐resolution Pleiades satellite and drone imagery that covered the entire western and middle sections of the 1920 Haiyuan earthquake rupture and compiled offsets reported on the eastern section from field measurements in the 1980s. Careful discrimination between single‐event and cumulative offsets suggests average horizontal slips of 3.0±1.0 m on the western section, 4.5±1.5 m on the middle section, and 3.5±0.5 m on the eastern section, indicating a total moment magnitude of M W =7.8±0.1. Thus, the seismological and geomorphological results agree within the uncertainties, a weighted average giving a moment magnitude of M W =7.9±0.2 for the 1920 Haiyuan earthquake. It is likely that earthquake magnitudes based on the historical M were systematically overestimated. Plain Language Summary: Earthquakes are the main mechanism by which elastic energy accumulating due to tectonic motion is released. As the earthquake magnitude scale is logarithmic, major earthquakes control the bulk of this energy budget and are often the most destructive, like the 1920 Haiyuan earthquake with ∼230, 000 casualties. However, major earthquakes tend to have recurrence periods of several hundred years, longer than our instrumental records. To obtain knowledge of historic major earthquakes, paleoseismologists measure geomorphic offsets and map surface ruptures left by past events and estimate the shaking intensity from historical writings. However, in the case of the Haiyuan earthquake, which happened in the late historic, early instrumental period, the magnitudes reported from these two communities differed significantly. In order to constrain the magnitude of this earthquake for seismic hazard assessment and to reconcile the differences between published magnitudes, we reestimated its magnitude from both newly compiled and digitized seismological records and modern satellite and drone imagery. The results show that the early seismological magnitudes were overestimated, which may affect historical magnitudes systematically. The 1920 Haiyuan earthquake was of a similar magnitude to the 2001 Kokoxili and 2008 Wenchuan earthquakes that also occurred in and around the Tibetan Plateau, instead of more than half a magnitude larger. Key Points: The often quoted magnitudes M 8.7 and M S 8.5 for the 1920 Haiyuan earthquake are overestimated Reanalyzing historical seismograms gives M W =7.9±0.2 and m B =7.9±0.3 Surface slip distribution and rupture length reviewed in 0.7‐m Pleiades imagery give M W =7.8±0.1